Pyrolysis-GC-MS-Olfactometry: A new approach to identify thermally generated odorants in frankincense - Niebler, Johannes; Büttner, Andrea (Journal of Analytical and Applied Pyrolysis, 2015)
Abstract Pyrolysis-GC-MS coupled with olfactometric detection represents a promising new instrumental approach for observing the generation of odor-active compounds from the non-volatile fraction of complex sample materials. The possibility to eliminate the volatiles already present in the sample by a thermal desorption prior to pyrolysis is particularly beneficial with the use of a filament-type pyrolyser. This is exemplified by an investigation of frankincense, the resin of Boswellia sacra Flueck. A variety of thermally generated odor active substances, absent in the native material, could be detected by this approach, which would otherwise be covered by volatiles from the sample material. A fractionation of the material by solvent extraction and high vacuum distillation allowed to further narrow down the origin of the pyrolytically generated compounds. Additionally, repeated thermal desorption at mounting temperatures from 120 to 300 °C followed by a pyrolysis run at 500 °C monitored the release and generation of compounds from the sample. This new approach is highly efficient and convenient not only for the investigation of incense materials, but also for off-odor generation in thermally strained materials, investigation of smoke flavor generation and related topics.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.pyroly
Keywords: Boswellia; Frankincense; Incense burning; Odor; Olfactometry; Py-GC-MS